1979
DOI: 10.1039/f19797500314
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen oxidation catalysed by X zeolite containing transition metal ions

Abstract: The catalytic activity of X zeolite for the oxidation of 1 % Halair in a flow system was augmented by the exchange of 20 % of the Na+ for transition metal ions. The kinetics were first order in Hz pressure, and from the temperature required to maintain kl = 2.0 x 1013 molecules g-' s-l Pa-' the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 0 publications
4
8
0
Order By: Relevance
“…It can be observed that the activities of MeZSM-5 were in the order: CuZSM-5>FeZSM-5>NiZSM-5. This order is in agreement with the orders in X-type and Y-type zeolites [21,23]. In those papers, they correlated the reaction activity with the content of reactive oxygen presented in Me-O-Me bridges.…”
Section: Combustion Of Hydrogen Over Mezsm-5supporting
confidence: 83%
See 2 more Smart Citations
“…It can be observed that the activities of MeZSM-5 were in the order: CuZSM-5>FeZSM-5>NiZSM-5. This order is in agreement with the orders in X-type and Y-type zeolites [21,23]. In those papers, they correlated the reaction activity with the content of reactive oxygen presented in Me-O-Me bridges.…”
Section: Combustion Of Hydrogen Over Mezsm-5supporting
confidence: 83%
“…On the other hand, two reduction steps of Cu 2+ to Cu + and Cu + to Cu ° in CuZSM-5 can be further demonstrated from the ratio (which was close to 1) of the first TPR band area to the second band area. Two similar reduction steps were also observed in X-type zeolite by Mahoney et al [21] and in Y-type zeolite by Jacobs et al [22].…”
Section: Tpr Of Mezsm-5supporting
confidence: 77%
See 1 more Smart Citation
“…According to the literature [22][23][24], the reduction of unsupported or supported Fe 2 O 3 to metal Fe 0 occurs in three steps below 630 • C, with Fe 3 O 4 and FeO as the intermediates. The reduction of Fe 3+ species to metal Fe 0 in the charge compensation sites of zeolite requires the temperatures above 730 • C, but that of Fe 3+ to Fe 2+ is observed to occur at lower temperatures [25][26][27]. Therefore, the former two peaks could be assigned to the reduction of Fe 2 O 3 "clusters" to metal Fe 0 , with Fe 3 O 4 as intermediate species [28,29], and the third one corresponding to the reduction of Fe 3+ to Fe 2+ [30,31], where Fe 3+ species come from the oxidation of ion-exchanged Fe 2+ ions into zeolite by calcinations [32].…”
Section: Temperature-programmed Reduction Testsmentioning
confidence: 92%
“…In the case of Cu 5 H-Z, the obtained signal with maximum at 310 °C was greater than the signal registered for Cu 5 Na-Z with maximum localized at 320 °C. In all cases the obtained wide reduction peaks may be assigned to Cu 2+ →Cu 0 [ 51 , 52 , 53 , 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%